Textos Multimodais e Letramento: habilidades na leitura de gráficos da Folha de São Paulo por um grupo de alunos do ensino médio - Viviane Martins Duarte (2008)
The growing presence of the image in verbal communication, especially in the media, raised the interest for multimodal texts, such as the graphic for the object of study. Despite the little attention which linguistic studies give to this textual genre, I searched for references in psychology in relation to mathematical education, and consequently found out that it would be possible and interesting to contribute to the reading of graphics, approaching them in relation with another genre, the news. I define the graphic as a textual genre, not only an illustration added to the verbal text. I also problematize it as a tool for education, according to a survey in which 55 subjects were interviewed. This survey showed that in schools the graphics are read in courses in the hard sciences and they are not part of the Portuguese language courses; nonetheless, the use of this genre is relatively effective outside the school environment, during the reading of newspapers and magazines. With this information raised in the analysis of this survey, I intended to follow the procedures of that research, in which 45 subjects did the reading of graphics isolated from the newspaper (version of the presentation G) and graphics presented in Folha de São Paulo (version of presentation GN). Further, each of the subjects answered 24 questions, which evaluated the development of 9 reading skills in the versions of presentations mentioned earlier. The general aim was to investigate the performance of the subjects in the skills related with the reading of the graphics, also verifying if these different forms of presentation of graphics would affect the input production. After collecting the results, I did the quantitative analysis, including the statistics tests, and qualitative analysis. The statistic analysis showed that the skill in which the subjects performance was more successful was the ability of recognizing the referents of graphic elements. Statistically, the percentage of successful answers was considered high in all the abilities. Analyzing the answers collected in terms of quantity, I found out that comprehension is more effective when the graphic is presented to reader in social conditions of circulation; that is to say, when it is related to another text that carried informative purposes as, for example, the news. This research attempted to contribute to the encouragement of a multimodal textual approach in schools that attempt to avoid the total disjoint (inevitably up to a certain point) between the multimodal texts and their social manifestations in the modes of communication. This thesis, therefore, has the purpose of enlightening the vision about the reading of a genre which is still little explored in the textual linguistics, and of raising questions about the multimodality in the contact between graphic and news in the discourse of information.